2015
DOI: 10.1016/j.adengl.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy in the Treatment of Melanoma Skin Metastases: A Report on 31 Cases

Abstract: Electrochemotherapy is a very effective, safe, and efficient treatment for advanced locoregional disease in patients with unresectable melanoma lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Six of them were excluded from the final analysis for the following reasons: one letter to editor, one case report, one with no data on tumor response, one without separated data on ECT, one reporting on the same patients population of a more recent study by the same authors, and one reporting on primary MM. Seven studies had a retrospective design [16][17][18][19][20][21][22], ten were prospective [11,12,[23][24][25][26][27][28][29][30] and one was a retrospective-prospective analysis [31]. Six studies were published before ESOPE guidelines were issued in 2006 [16-18, 23, 24, 26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of them were excluded from the final analysis for the following reasons: one letter to editor, one case report, one with no data on tumor response, one without separated data on ECT, one reporting on the same patients population of a more recent study by the same authors, and one reporting on primary MM. Seven studies had a retrospective design [16][17][18][19][20][21][22], ten were prospective [11,12,[23][24][25][26][27][28][29][30] and one was a retrospective-prospective analysis [31]. Six studies were published before ESOPE guidelines were issued in 2006 [16-18, 23, 24, 26].…”
Section: Resultsmentioning
confidence: 99%
“…Most lesions were in the trunk and extremities. The size of the treated metastases was reported heterogeneously: some authors reported the volume [11,16,23,24], others the diameter [12,18,19,21,[25][26][27][28][29][30], while four papers did not describe this data [17,20,22,31]. Looking at the diameter, the range was 2-260 mm.…”
Section: Patients and Tumors Characteristicsmentioning
confidence: 99%
“…The adverse effects of electrochemotherapy seem to be mild and transient. In most of the studies, complications such as erythema, oedema, and pain appeared immediately and resolved after a few days [108]. Late side effects and systemic toxicity were also mild due to low chemotherapy drug doses [108].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies, complications such as erythema, oedema, and pain appeared immediately and resolved after a few days [108]. Late side effects and systemic toxicity were also mild due to low chemotherapy drug doses [108]. Post-procedure pain seems to be associated with moderate or severe pain before treatment, size of the largest treated lesion, previous irradiation, and a high level of current [15,22,85,101].…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation (EP) or the drugs on their own do not influence the growth of tumors, but the combination of the EP and bleomycin has potent antitumor effects. In previous reports, ECT has shown to be effective as palliative treatment of cutaneous and subcutaneous metastases in patients with cutaneous melanoma [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%